Practical column design guide - Nitsche, M.; Gbadamosi, R. (Springer, 2017)
This book highlights the aspects that need to be considered when designing distillation columns in practice. It discusses the influencing parameters as well as the equations governing them, and presents several numerical examples. The book is intended both for experienced designers and for those who are new to the subject.
Keywords: Distillation apparatus -- Design and construction.; Distillation -- Design and construction.; elektronické knihy; electronic books